Reflections on the experiences of a group of emerging-adult violent offenders and the value of interventions in navigating their lives - Stewart, Grant Charles (Stellenbosch : Stellenbosch University, 2020)
Thesis (MEdPsych)--Stellenbosch University, 2020.